The Antibody Drug Absorption Following Subcutaneous or Intramuscular Administration and Its Mathematical Description by Coupling Physiologically Based Absorption Process with the Conventional Compartment Pharmacokinetic Model. (20th February 2013) - Zhao, Liang; Ji, Ping; Li, Zhihong; Roy, Partha; Sahajwalla, Chandrahas G.
Abstract The main objective of this paper is to propose a quantitative model to describe the absorption process for monoclonal antibody (mAb) following subcutaneous (SC) or intramuscular (IM) administration. A hybrid model was established by coupling the physiologically based absorption process with a conventional pharmacokinetic–pharmacodynamic (PK–PD) or PK model associated with intravenous infusion. Key physiological parameters evaluated include the volume distribution before systemic absorption, mAb drug clearance during lymphatic transport, the neonatal Fc receptor (FcRn) capacity, the intrinsic drug clearance via lysosomal proteolytic process, and the lymphatic flow rate. Sensitivity analyses were performed to identify those physiological parameters significantly impacting time to peak concentration (Tmax) or drug bioavailability. Simulation results showed that lymphatic flow rate is the only influential factor to Tmax. Lymphatic transit time and drug clearance during lymphatic transport are most influential to bioavailability but not identifiable in their effects. Bioavailability is positively related to the lymphatic flow only at its low range (i.e., at <0.5‐fold of the selected value of 0.043 mL/min). The rest of physiological parameters only have marginal effects on either drug bioavailability or Tmax. Finally, simulation results confirmed lymphatic transport as the major route of mAb delivery.